2019
DOI: 10.1186/s13046-019-1216-x
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery of sorafenib and metapristone encapsulated by CXCR4-targeted PLGA-PEG nanoparticles overcomes hepatocellular carcinoma resistance to sorafenib

Abstract: Background Sorafenib is approved as a standard therapy for advanced hepatocellular carcinoma (HCC), but its clinical application is limited due to moderate therapeutic efficacy and high incidence of acquired resistance resulted from elevated levels of SDF-1/CXCR4 axis induced by prolonged sorafenib treatment. We previously demonstrated metapristone (RU486 metabolite) as a cancer metastatic chemopreventive agent targeting SDF-1/CXCR4 axis. Therefore, we hypothesized that combining sorafenib with me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…Based on the results reported before, we decided to use only the two smallest concentrations of GA, together with different concentrations of Doxo. This type of protocol, where one of the drugs has a fixed concentration and the concentration of the second one is varied, has been applied successfully for different drug combinations, as reported in the literature [31][32][33][34]. Furthermore, in order to assess if the combination of the two drugs has a synergistic effect, we calculated the combination index (CI) and found that all conditions tested were synergistic (CI < 1).…”
Section: Synergetic Effect Of Doxo and Ga Treatments On Ht-29 Spheroidsmentioning
confidence: 99%
“…Based on the results reported before, we decided to use only the two smallest concentrations of GA, together with different concentrations of Doxo. This type of protocol, where one of the drugs has a fixed concentration and the concentration of the second one is varied, has been applied successfully for different drug combinations, as reported in the literature [31][32][33][34]. Furthermore, in order to assess if the combination of the two drugs has a synergistic effect, we calculated the combination index (CI) and found that all conditions tested were synergistic (CI < 1).…”
Section: Synergetic Effect Of Doxo and Ga Treatments On Ht-29 Spheroidsmentioning
confidence: 99%
“…At temperatures below the lower critical solution temperature, these materials are in a sol state with a low viscosity, but they enter a gel state at higher temperatures 53 . Thermosensitive hydrogels are promising drug carriers because of their biodegradability, low toxicity, high drug loading capacity, site specificity, sustained release, controlled release, and other advantages 54 . For example, Zheng et al synthesized a thermosensitive composite NP that was used as an effective drug carrier for SOR and was combined with radiotherapy for local and continuous treatment of liver cancer 55 .…”
Section: Enhancing the Biocompatibility Of Sor With Npsmentioning
confidence: 99%
“…Metapristone (RU486 metabolite) is a metastatic chemopreventive agent targeting the SDF-1/CXCR4 axis 106 . Zheng et al encapsulated SOR and metapristone in a hydrophobic nucleus through hydrophobic interactions between the drugs and PLGA-PEG-COOH (Figure 6 ) 54 . The LFC131 peptide was covalently bound to the surface of the NPs to target CXCR4, and SOR and metapristone were simultaneously delivered to CXCR4-expressing HCC cells.…”
Section: Targeted and Responsive Delivery Of Sor With Npsmentioning
confidence: 99%
“…10,13 Zheng et al verified co-delivery of sorafenib and metapristone by the LFC131-conjugated (a peptide inhibitor of CXCR4) PLGA NPs showed prolonged circulation and target accumulation at tumor sites, and thus suppressed tumor growth in HCC models. 14 Byeon et al developed HA-labeled PLGA NPs (HA-PLGA NPs) incorporating both PTX and FAK siRNA as a two-in one delivery system to increase the efficiency of targeted delivery against tumor-specific receptors and to enhance therapeutic efficacy in drug-resistant ovarian cancer. 15 In comparison to monotherapy, anticancer drugs encapsulated in PLGA nanoparticles show good biocompatibility, strong cytotoxicity, significant antitumor activity and minimal systemic toxicity.…”
Section: Plga-based Nanoparticlesmentioning
confidence: 99%